Analisis Tindak Tutur Lokusi Pada Teks Prosedur Dalam Buku Bahasa Indonesia Kelas XI Kurikulum 2013 - Estri Sal Sabila Asmaning Trias; Astri Kusuma Dewi; Aisyah Mudjahidah; Alfarell Fadhil Waradana; Galan Anugerah Novanto; Rio Anugrah Rizkiansyah; Asep Purwo Yudi Utomo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research analyzes the speech acts of procedure text contained in the Indonesian language textbook class XI Curriculum 2013. The approach that analyzes in this research is methodological which applies descriptive qualitative and theoretical approaches to analyze locutionary speech acts using analytical approaches in the field of pragmatics. In addition, agih method is also used. The data were obtained and collected by means of data collection techniques in the form of listening and recording steps. The initial stage was to read the existing procedure text carefully, in detail and thoroughly. Then, by detailing the sentences that include locutionary speech acts in the procedure text. After the data is collected, the data is analyzed by using agih method and interactive analysis. Furthermore, the data presentation is included in the research using informal methods. This research presents the data in the form of tables and the results of the discussion are presented in the form of sentences. The results of this analysis take declarative, imperative, and interrogative locutionary speech acts as three different categories of locutionary speech acts. The three types of locutionary speech acts get a total of 21 data with the following details, 7 declarative locutionary speech acts, 4 interrogative locutionary speech acts and 10 imperative locutionary speech acts. Hopefully, this research can help researchers and readers to increase knowledge related to locutionary speech acts or matters related to analysis.